2019
DOI: 10.30659/ijibe.4.1.540-550
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sharia Banking Characteristics and Macroeconomics Factors on Sharia Banking Profitability: Empirical Studies in Indonesia

Abstract: This research aims to examine the influence of sharia banking characteristics (CAR, FDR, BOPO and NPF) and macroeconomics factors (inflation and GDP) on sharia banking profitability (return on asset/ROA). The data was obtained from the Financial Services Authority (OJK) publication report by purposive sampling technique in 12 sharia commercial banks. Then, data were analysed by multiple linear analysis. The results indicate that variables of BOPO, NPF and GDP significantly influence the ROA, but FDR, CAR and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 4 publications
5
6
0
1
Order By: Relevance
“…Research by Rofiqo & Afrianti (2019) shows that some NPF financing problems harm profitability; this is in line with the study of Indyarwati & Handayani (2017) and Afrizal (2017, p. 207). Negative impact on company performance.…”
Section: Literature Reviewsupporting
confidence: 80%
See 1 more Smart Citation
“…Research by Rofiqo & Afrianti (2019) shows that some NPF financing problems harm profitability; this is in line with the study of Indyarwati & Handayani (2017) and Afrizal (2017, p. 207). Negative impact on company performance.…”
Section: Literature Reviewsupporting
confidence: 80%
“…It is in line with Mahmudah & Harjanti (2016) and Yusuf (2017), which show that CAR has a significant positive effect on profitability. As for research conducted by Indyarwati & Handayani (2017) and Syakhrun et al (2019), Quan et al (2019), Almazari (2014), Duraj & Moci (2015), Mohamad, Sulaiman, Hamimah, & Muslim (2019), Anwar Salem Musibah & Wan Sulaiman Bin Wan Yusoff Alfattani (2017), Al Zaidanin (2020), and Hazzi & Kilani (2013) shows that CAR is beneficial for profitability (ROA) has a negative effect Research conducted by Rofiqo & Afrianti (2019) shows that CAR does not have a significant effect on profitability (ROA). With the following assumptions: H1: Capital Adequacy Ratio (CAR) has a positive impact on the performance of Islamic commercial banks.…”
Section: The Effect Of Car On the Performance (Roa) Of Islamic Commercial Banksmentioning
confidence: 96%
“…This can happen because the increase in nonperforming financing can potentially reduce the income that comes from financing products. Several studies found a negative effect of NPF on ROA (Yusuf and Mahriana, 2016;Harianto, 2017;Azmy, 2018;Sutrisno and Widarjono, 2018;Rofiqo and Afrianti, 2019;Istiqomaha et al, 2021). On the other hand, studies by Said and Ali (2016), Virgana et al (2019), and Wahyudi (2020) found that NPF does not affect ROA.…”
Section: H2: Non-performing Financing (Npf) Hurts Bprs Profitabilitymentioning
confidence: 99%
“…Research by Almunawwaroh and Marliana (2018), Sari and Endri (2019), as well as Alnajjar and Abdullah Othman (2021), found that CAR hurts ROA, contrastingly the research by Alshatti (2016), Virgana et al (2019), Wahyudi et al (2019) and Bouhider (2021) found a positive effect of CAR on the ROA of Islamic banks in Indonesia. Some researchers found that CAR does not affect the ROA value of BPRS (Said and Ali, 2016;Harianto, 2017;Sutrisno and Widarjono, 2018;Azmy, 2018;Rofiqo and Afrianti, 2019;Wahyudi, 2020;Rachmadani et al, 2021).…”
Section: H1: Capital Adequacy Ratio (Car) Hurts Bprs Profitabilitymentioning
confidence: 99%
“…Apabila rasio ROA meningkat maka rasio FSR juga akan mengalami kenaikan. Hal tersebut didukung pada penelitian yang dilakukan Sari & Haryanto (2017) dan Rofiqo & Afrianti (2018) bahwa NPF berpengaruh terhadap ROA dan Nurhikmah (2021) bahwa ROA berpengaruh terhadap FSR.…”
Section: Return On Asset (Roa)unclassified